Efficacy, Safety, and Antimicrobial Activity of a Polyherbal Formulation (Ocemic Capsule) in the Treatment of Otitis Media: A Single-Blind Randomized Controlled Clinical Trial - Dr. Gajanan Patil,Dr. Mayuri Mane,Digambar Jadhav (South Eastern European Journal of Public Health, 2025)
the present study aimed to assess the antimicrobial effect and safety of proprietary polyherbal formulation labelled as Ocemic capsule on otitis media in ear. It is A single blind randomized, controlled clinical study in institutional setting Post Ethics Committee permission, screened otitis media, both ASOM and CSOM patients of either sex aged 20-60 years were randomized to trail group and controlled group for 11 days. Major assessment variables included Culture and sensitivity, audiological evaluation by Audiometry (PTA) and effect on symptoms otorrhea otalgia and changes in perforation. All selected patient were observed till 11 days in both groups, screening was done on day 0 for inclusion in study patients fulfilling inclusion criteria were randomized into either group and follow up on 3rd, 6th, 9th,11th. From day 1 drug will be started up to day days on 11-day patient will be assed for after trail results. Audiometry was done on 0th and 11th day Mean ± standard deviation median (range) and Wilcoxon Rank sum test/Mann–Whitney test for nonparametric data analysis, were done. For pain parameter normality does not satisfy hence used Wilcoxon test instead of “t test” GraphPad IN Stat software, version 9 was used with p < 0.05, as the level of statistical significance. The primary outcomes included the resolution of key symptoms (pain, ear discharge, tympanic membrane perforation), audiometric improvements, and microbial culture sensitivity. Results revealed that Ocemic capsule significantly outperformed cefixime in reducing pain, ear discharge, improving hearing, and promoting tympanic membrane healing. The formulation demonstrated notable antimicrobial activity, suggesting its potential as a safe, effective alternative to conventional antibiotics in treating otitis media.